REVIEW : PATOGENESIS DAN DIAGNOSA LABORATORIUM DEMAM TIFOID - Nurmaidah Nurmaidah; Dian Nurmansyah (LPPM Universitas Abdurrab, 2020)
Typhoid fever caused by the pathogen bacteria named Salmonella typhi is known to have caused the death of more than 600,000 people worldwide. Understanding the pathogenesis and proper laboratory examination is very influential on the success of therapy. This literature review aims to collect literature related to pathogenesis and laboratory examination in typhoid fever. This literature review method uses the Systematic Literature Review (SLR) model based on pathogenesis and laboratory examinations. S. typhi infection begins with the entry of bacteria through the gastrointestine tract and can last up to 3 weeks. Laboratory tests for typhoid fever are bacterial culture, serological examination, molecular examination, and other investigations. Bacterial culture is a gold standard that has a sensitivity of up to 80% in blood. Serological tests can be performed such as Widal, ELISA, SDS-PAGE blotting, RDT or POCT tests using venous blood, capillary blood, even serum, and typhidot, and Tubex TF. Other investigations can be characterized by leukocytosis and eosinopenia. Blood chemistry tests also found an increase of AST and ALT 2-3 times the normal value.